Brexit between EU-Remainers and Pro-Brexiteers’ Communities on Social Media: a Socio-cognitive Approach of Facebook and Twitter Discourses - BELGAID, Nazim (l’Université de Mostaganem, 2022)
This research project deals with the way Brexit is perceived in the UK by both the pro-Brexit proponents and partisans of the European Union (EU) via discourse. What emerges anew is the discursive controversy on line. In fact, virtual communities have become an intrinsic feature in this digital age. With the rapid rise of SNSs worldwide, a novel form of representing shared knowledge about the world and determining relations of power and dominance between online communities has arrested attention across a myriad of disciplines, notably DA. In the study, we set forth with the very aim of applying Van Dijk’s CDA-oriented theory of social cognition (SC) in analytically approaching the respective discourses of some selected pro-Brexiteers alongside, EU-remainers’ communities on both Facebook and Twitter. We refer to such theoretical terms as discourse, cognition, social cognition, social representations (SRs), structures of power, ideology, and domination; we deploy them in the analytical process as well. The results have revealed that the discourse of the pro-Brexiteers communities is dominant on both platforms with their ideological implications having concrete effects in that the UK is being pushed toward complete Brexit. At once, the EU-remainers resist discursively trying to make their shared schemata of ideologies favorable to the EU heard on the national scene. Thus, power and domination/struggle and resistance/status quo/subversion are at work on the virtual space.
Keywords: social cognition, discourse, pro-Brexiteers and EU-remainers communities, Facebook, and Twitter.